Valentina Di Napoli, Francesco Camia, Vasilis Evangelidis, Dimitris Grigoropoulos, Dylan Rogers, and Stavros Vlizos (eds) What’s New in Roman Greece: Recent Work on the Greek Mainland and the Islands in the Roman Period (Meletemata 80). - Erskine, Andrew (Journal of Greek Archaeology, 2023)
pp. xxviii + 63,. 16 colour plates. Athens, 2018. ISBN: 9789609538794. €110.